Role of Mucoadhesive Microspheres as Intra-nasal Drug Delivery - Rama Rao Tadikonda; Aditya Anand (Shiraz University of Medical Sciences, 2024)
Carrier technology offers a innovative method for medication distribution by connecting drugs to carrier particles like liposomes, nanoparticles, or microspheres. Microspheres, with their small size and effective characteristics, are crucial in this particle medication delivery method. Mucoadhesive microspheres achieve better drug absorption by sticking to the mucosal surface and releasing the medication over an extended period. Microspheres are spherical, freely flowing, made of natural or synthetic polymers with a particle size range of 1-1000μm. Due to their unique size-dependent property and ability to include medications in carriers, lipid microspheres offer potential for novel treatments. There are several methods for preparing microspheres and releasing the medication at the intended site of action in a steady and regulated way. Due to their enhanced half-life, oral delivery capabilities, and better therapeutic responses, microspheres have gained interest in targeting and treating various illnesses. This article reviewed about the mucoadhesive microspheres, its mechanism, preparation methods and also the recent trends being achieved on mucoadhesive microspheres.